Head Start Parents With or Without Food Insecurity and With Lower Food Resource Management Skills Use Less Positive Feeding Practices in Preschool-Age Children - Na, Muzi (J Nutr, 2021)
BACKGROUND: Food resource management (FRM), strategies to stretch limited food resource dollars, may mitigate the impact of household food insecurity (HFI) on family members, including young children. However, little is known about how FRM and HFI are associated with child feeding practices. OBJECTIVES: The study aimed to explore relationships between HFI, FRM, and child feeding practices of low-income parents. METHODS: In a cross-sectional sample of 304 Head Start households, caregivers completed the USDA HFI module [classifying them as either food secure (FS) or food insecure (FI)], FRM behavior subscale (classifying them as being high or low in management skills based on a median score split), Comprehensive Feeding Practices Questionnaire, and Perceived Stress Scale. Households were categorized into 4 HFI-FRM subgroups: FS/high FRM (30.6%), FS/low FRM (31.3%), FI/high FRM (18.8%), and FI/low FRM (19.4%). Multivariable linear regression was used to examine whether feeding practices differed across HFI-FRM categories and whether the addition of parental perceived stress contributed to differences in feeding practices by HFI-FRM group. RESULTS: In our study, 38% of households were FI. Compared to the FS/high FRM group in the adjusted models, the FS/low FRM group used less monitoring (−0.53; 95% CI: −0.78 to −0.28), modeling (−0.38; 95% CI: −0.64 to −0.13), and involvement (−0.57; 95% CI: −0.82 to −0.32) in feeding. A similar pattern emerged for the FI/low FRM group. The use of food as a reward was higher in the FI/high FRM (0.35; 95% CI: 0.02–0.67) and FI/low FRM groups (0.33; 95% CI: 0.01–0.66) compared to the FS/high FRM group. Perceived stress was positively associated with the use of negative, controlling feeding practices, and contributed to differences in using food as a reward within the HFI-FRM group. CONCLUSIONS: Suboptimal child feeding is evident in low-income caregivers with low FRM skills, with or without food insecurity. Promoting high FRM skills, in addition to addressing food insecurity, could potentially synergistically improve child feeding practices in low-income households.